Low degree of substitution of cellulose acrylate based green polyelectrolyte: Synthesis, characterization and application to the removal of Cu (II) ions and colloidal Fe(OH)3 turbidity. (2020) - Chaouf, Sara; El Barkany, Soufian; Amhamdi, Hassan; Jilal, Issam; El Ouardi, Youssef; Abou-salama, Mohamed; Loutou, Mohamed; El-Houssaine, Ablouh; El Ouarghi, Hossain; El Idrissi, Abderahmane
Abstract: The uncontrolled radical grafting of acrylamide on cellulose generates a disorderly size distribution of grafted and ungrafted (as a by-product) PAM chains, which required additional purification steps. At this stage, the anionic grafting appears as a well-controlled grafting method of acrylic entities on the cellulosic backbone, using alkali alkoxylation to increase the reactivity of OH-cellulosic groups, and water as transfer agent for hydrogen to stop chain extension and to prevent the formation of polyacrylamide. Based on this mechanism, low Degree of Substitution of cellulose acrylate was elaborated in NaOH/Urea/H2O and used as low-cost, eco-friendly and nontoxic water-soluble polymers. The proposed synthesis were confirmed using (FTIR-ATR) and (1H NMR and 13C NMR). However, SEM-EDX and XRD shows the effect of the incorporation of acrylate entities on the morphology, the surface composition and the crystalline order of cellulose, respectively. Flocculation-coagulation study, according to the effect of various experimental parameters (pH, reaction time, flocculant concentrations, etc.), showed an excellent capacity to heavy metals ions removal (qeCu2+ = 400 mg.g-1) and to cationic colloïdal systems clarification (99% to Fe(OH)3) at neutral conditions (pH7).